Apakah Cognitive Behaviour Therapy (CBT) Digital Efektif untuk Menurunkan Kecenderungan Bunuh Diri pada Gen Z? - Kamsih Astuti; Sheilla Varadhila Peristianto; Albert Yacobus Chandra (Bulletin of Counseling and Psychotherapy, 2026)
Suicide is a serious problem in society and has now become a global concern. Although suicide is a serious public health issue, it can be prevented with the right interventions. Cognitive behavioral therapy (CBT) is a psychological intervention that is quite effective in reducing suicidal ideation; however, the limited availability of psychologists prevents this method from reaching a wider audience. These conditions present an opportunity for the use of internet-based CBT as an alternative for addressing suicidal tendencies among Gen Z. This study was conducted to evaluate the Digital CBT program (Mindspace Program) for preventing suicidal tendencies in Gen Z. Web-based psychological interventions will enhance the accessibility and reach of the program. The research subjects were 10 Gen Z individuals, aged 22–26 years. This study employed a one-group pre-test - post-tests design with the Mindspace Programme as the intervention. The research instrument utilized the Suicide Tendency Scale, administered during the pre-test, post-tests, and follow-up. The results were analyzed using a paired samples t-test, revealing a significant difference in suicidal tendencies among the participants before and after receiving Digital CBT, with a t-value of 5.137 (p < 0.01). Suicidal tendencies were lower after Digital CBT (mean: 29.00) compared to before Digital CBT (mean: 37.46). These findings imply that digital CBT is an effective alternative for addressing suicidal tendencies among Gen Z and serves as an evidence-based intervention.